58th AIAA/ASCE/AHS/ASC Structures, Structural Dynamics, and Materials Conference 2017
DOI: 10.2514/6.2017-0405
|View full text |Cite
|
Sign up to set email alerts
|

High Speed Vehicle Fluid-Structure-Jet Interaction Analysis and Modeling

Abstract: This paper presents high-fidelity solutions of the fluid-structure-jet interaction problem for slender high-speed vehicles along with two jet interaction modeling methods, one semiempirical and one CFD-based, to approximate the high-fidelity solution. The high-fidelity solutions of a representative high-speed vehicle with jet interaction and structural deformation show that the resultant loads are affected by the deformation. The semi-empirical jet interaction model is developed using previous work in the lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In addition, the attitude jet thrust has a range that is sufficient to counter-act the aerodynamic stiffness of the vehicle leading to very large angles above 90 degrees. However, from previous work by the authors 17 it is shown that there is a nonlinear transition between the jet interaction with a windward and leeward facing jet, which occurs near zero angle of attack of a rotating vehicle. The dynamic transition between windward and leeward is expected to be more significant and is the subject of the current work compared to the dynamic effects at very high angles of attack.…”
Section: A Jet Interaction Sensitivitymentioning
confidence: 94%
See 1 more Smart Citation
“…In addition, the attitude jet thrust has a range that is sufficient to counter-act the aerodynamic stiffness of the vehicle leading to very large angles above 90 degrees. However, from previous work by the authors 17 it is shown that there is a nonlinear transition between the jet interaction with a windward and leeward facing jet, which occurs near zero angle of attack of a rotating vehicle. The dynamic transition between windward and leeward is expected to be more significant and is the subject of the current work compared to the dynamic effects at very high angles of attack.…”
Section: A Jet Interaction Sensitivitymentioning
confidence: 94%
“…The aerodynamic interference model was based on a series of steady-state solutions, which would not capture any of the dynamic aspects during flight simulations. Kitson and Cesnik 16,17 have developed a flexible high speed vehicle model with a reaction control system to maneuver the vehicle during flight simulations within a coupled modeling and simulation framework. However, the JI model was based on steady-state solutions that do not account for the dynamic flight environment or the transient forces due to varying jet pressure.…”
Section: Introductionmentioning
confidence: 99%